The contribution of Angola to the early spread of the HIV-1 epidemic - Pineda-Peña, Andrea-Clemencia; Varanda, Jorge; Theys, Kristof; Bártolo, Inês; Leitner, Thomas; Taveira, Nuno; Vandamme, Anne-Mieke; Abecasis, Ana B. (My University, 2015)
"Understanding how, when and why the HIV-1 virus adapted to the human population and become pandemic is crucial to prevent its propagation and the establishment of other potential future viral pandemics. It is known that the HIV-1 group M epidemic started in Kinshasa, Democratic Republic of Congo (DRC), and soon spread across the Congo river to Brazzaville located in Republic of Congo (RC), and further to Lubumbashi and Mbuji-Mayi (DRC), around 1930s (~1937 [95% Bayesian Credible Interval: 1919-1957]). Angola borders and has long-term links with DRC and RC as well as high levels of HIV-1 genetic diversity 2. Therefore, we aimed to investigate the role of this country in the initial spread of the HIV-1 pandemic."
Poster presented at the 22nd International HIV Dynamics and Evolution. Budapest, Hungary, 13-16 May 2015
Keywords: HIV-1 epidemic; Angola